U.S.-Hong Kong relations: Prospects for a unique partnership - GILL, Bates (Institutional Knowledge at Singapore Management University, 2007)
Hong Kong has survived turbulent economic, social and political changes in the past ten years since the former crown colony’s reversion to Chinese sovereignty. Following setbacks in the wake of the Asian financial crisis and the avian flu outbreak in 1997, the outbreak of severe acute respiratory syndrome (SARS) in 2003, and several massive political demonstrations in recent years, Hong Kong’s economy has had a robust and steady rebound. Hong Kong has maintained its position as a leading business and financial hub in the Asia-Pacific region and for the world. It has continued to play a pivotal role in China’s economic development with increasing economic and even social integration between the two. On the whole Hong Kong has remained politically stable, and retains its title as one of the freest and most open economies in the world.